The settlement mechanism of diagnosis-intervention packet payment scheme in China：A policy review and lessons learned - Qiang Yao; Xiaodan Zhang; Lan Yao (Informatics and Health)
The settlement of the medical insurance fund is the key point of the implementation of the big data diagnosis & intervention packet (DIP) under the regional global budget. This study proposed the framework with key methods for the settlement of DIP on medical insurance funds through on-site survey and policy literature analysis. The results show that the settlement framework, featuring “Fund pre-allocation”, “Monthly pre-settlement” and “Annual settlement”, integrates ideas of both the pre-payment system and post-payment system. “Monthly pre-settlement” being the key part of the settlement process, plays an important role in breaking down the year-end pressure of medical insurance management organizations and healthcare institutions, and guiding providers' reasonable behaviors. “Annual settlement” acts as the core link of settlement, which determines the annual medical insurance fund payment amount of healthcare institutions, which needs to rely on and integrate key elements such as regional global budget, DIP grouping database and correction, and healthcare institution supervision and assessment. The settlement process, measurement methods, and key parameters must be clarified by introducing settlement and related supporting policies, which provide technical support and institutional guarantees for the implementation and effectiveness of the DIP reform.